A Brief View of the ESP Approach - Barrantes Montero, Luis Guillermo (2009)
El artículo trata sobre el enfoque de inglés para fines específicos. Está dirigido a profesores de inglés general, aunque intenta también que la comunidad universitaria reconozca la importancia de evaluar la inversión de recursos en la enseñanza del inglés en función de sus resultados concretados. Se ofrece una descripción de las condiciones que se requieren para diseñar y efectuar estos cursos, acompañada de comentarios surgidos a partir de la experiencia del autor.This article provides information about the English for Specific Purposes (ESP) Approach. Although it is intended for teachers of General English, it also aims for the university community as a whole to evaluate how resources are currently invested in English teaching, with regard to the results obtained. A description of the conditions required to design and implement those courses is presented, along with the author's comments based on his own experience.